Triplet state delocalization in a conjugated porphyrin dimer probed by transient electron paramagnetic resonance techniques - Tait, C; Neuhaus, P; Anderson, H; Timmel, C (American Chemical Society, 2015)
The delocalization of the photoexcited triplet state in a linear butadiyne-linked porphyrin dimer is investigated by time-resolved and pulse electron paramagnetic resonance (EPR) with laser excitation. The transient EPR spectra of the photoexcited triplet states of the porphyrin monomer and dimer are characterized by significantly different spin polarizations and an increase of the zero-field splitting parameter D from monomer to dimer. The proton and nitrogen hyperfine couplings, determined using electron nuclear double resonance (ENDOR) and X- and Q-band HYSCORE, are reduced to about half in the porphyrin dimer. These data unequivocally prove the delocalization of the triplet state over both porphyrin units, in contrast to the conclusions from previous studies on the triplet states of closely related porphyrin dimers. The results presented here demonstrate that the most accurate estimate of the extent of triplet state delocalization can be obtained from the hyperfine couplings, while interpretation of the zero-field splitting parameter D can lead to underestimation of the delocalization length, unless combined with quantum chemical calculations. Furthermore, orientation-selective ENDOR and HYSCORE results, in combination with the results of density functional theory (DFT) calculations, allowed determination of the orientations of the zero-field splitting tensors with respect to the molecular frame in both porphyrin monomer and dimer. The results provide evidence for a reorientation of the zero-field splitting tensor and a change in the sign of the zero-field splitting D value. The direction of maximum dipolar coupling shifts from the out-of-plane direction in the porphyrin monomer to the vector connecting the two porphyrin units in the dimer. This reorientation, leading to an alignment of the principal optical transition moment and the axis of maximum dipolar coupling, is also confirmed by magnetophotoselection experiments.